A cephalometric study of changes in point A under the influence of upper incisor inclinations. - (:unkn) unknown (My University, 1991)
Today the ANB angle is commonly used for defining the anteroposterior apical base relationships of the jaws. The factors that influence the ANB angle have been studied by various investigators. The axial inclination of the maxillary central teeth is one of the factors influencing the location of point A. In this study the relationship between the axial inclination of the upper central incisor and the location of point A was studied. Four criteria that define the location of the maxillary central teeth were used: I (incisal point), Ap (apical point), R (rotation point), and I-SN (angle between I and SN plane). A significant positive correlation was found between the location of points A and R. We also calculated a regression equation for this relationship.